1979
DOI: 10.1159/000232175
|View full text |Cite
|
Sign up to set email alerts
|

Humoral Immunoreactivity in Chronic Active Hepatitis: Relation to HLA Antigens

Abstract: 43 patients with chronic active hepatitis (CAH) exhibited significantly higher levels of antibodies against measles and polio type 2 und 3 when compared to 43 age- and sex-matched healthy controls. No significant differences were found for antibodies against polio type 1, rubella, herpes simplex, mumps virus, and tetanus. There was no correlation between antibody levels and the presence of HLA-B8 and/or HLA-B12. The antibody response to vaccination with polio vaccine (killed) and tetanus toxoid was not higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1979
1979
1983
1983

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Six patients with CAH had the cholestatic form of the disease and showed a poor response to the ordinary corticosteriod dose. These patients seemed to have more anti-MFs of IgM class (36) when compared to other patients with CAH (%a). Four anti-MF-positive sera were also tested using cells not subjected to drug treatment.…”
Section: Anti-mfsmentioning
confidence: 74%
“…Six patients with CAH had the cholestatic form of the disease and showed a poor response to the ordinary corticosteriod dose. These patients seemed to have more anti-MFs of IgM class (36) when compared to other patients with CAH (%a). Four anti-MF-positive sera were also tested using cells not subjected to drug treatment.…”
Section: Anti-mfsmentioning
confidence: 74%
“…Furthermore, because of the increased frequency of HLA-B8, which had been reported in populations of patients with hepatitis B-negative CAH (13), they postulated that this histocompatibility antigen might serve as a marker for a specific defect in suppressor T-cell function, although there was no good evidence in man that genes on Chromosome 6 controlling immune regulation were linked to genes coded in the HLA locus. Galbraith et al (14) reported increased levels of anti-bodies to rubella, measles, nuclei, and smooth muscle in patients with CAH with HLA B8 or B12, but these results were not confirmed by Lindberg et al (15,16). Since that time, alterations in immunoregulatory T-cell activity have been demonstrated in CAH (2-6) and there has been confirmation of the increased frequency of HLA-B8.…”
Section: Resultsmentioning
confidence: 97%